A Spiritual Pedagogic Approach to Learning (Analytical Study of Approach Model) - Masbur, Masbur (SCAD Independent, 2022)
This study aimed to explain a spiritual pedagogic approach. Spiritual pedagogy is a field of research that obstructs experience, knowledge, and intuition through the activities of touching, discussion, and reflection until it gives birth to certain values that then encourage, encourage, excite, enlighten, - and become the basis for the holder of that value in pursuing his profession as an educator, teacher, or parent. The research method used in this study was qualitative, namely research that produces descriptive data in the form of written or spoken words from the observed behavior. The results showed that the spiritual pedagogic approach model in learning through the implementation of fostering students' spiritual attitudes and the pattern of implementing the spiritual pedagogic approach model.